Anti-Microbial Activities of Soya Protein Isolate (SPI) Cloisite C30b (MMT) Nanocomposite Film - Biswal, Susanta Kumar (Journal of Asian Scientific Research, 2012)
In the present research program, the anti-bacterial properties of Soya Protein blended with Cloisite 30 B have been investigated. The nanocomposite films were prepared blending it with Cloisite 30 B. The composites were characterized by Fourier Transmission Infra Red Spectroscopy (FTIR), X-Ray Diffraction (XRD) analysis. The morphology of the nanocomposites was ascertained from the SEM studies. The polymers were tested for anti-microbial activity against Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli). The SPI/C30B nanocomposite films strongly inhibited the growth of a wide variety of microorganisms including Gram-positive bacteria, Gram-negative bacteria. The anti-microbial studies were carried out against food borne pathogens. The biodegradability of the nanocomposites has also been reported.